Introduction: Situating mixed race in New Zealand and the world - Webber, Melinda (Mana Tangatarua: mixed heritages, ethnic identity and biculturalism in Aotearoa/New Zealand, 2018)
"This volume explores mixed race/mixed ethnic identities in Aotearoa/New Zealand. Mixed race and mixed ethnic identity are growing in popularity as research topics around the world. This edited collection looks at mixed race and mixed ethnic identity in New Zealand: a unique context, as multiple ethnic identities have been officially recognised for more than 20 years. The book draws upon research across a range of disciplines, exploring historical and contemporary ways in which official and social understandings of mixed race and ethnicity have changed. It focuses on the interactions between race, ethnicity, national identity, indigeneity and culture, especially in terms of visibility and self-defined identity in the New Zealand context. Mana Tangatarua situates New Zealand in the existing international scholarship, positioning experiences from New Zealand within theoretical understandings of mixedness. The chapters develop wider theories of mixed race and mixed ethnic identity, at macro and micro levels, looking at the interconnections between the two. The volume as a whole reveals the diverse ways in which mixed race is experienced and understood, providing a key contribution to the theory and development of mixed race globally."--Provided by publisher.
Keywords: bicultural; ethnic identity; ethnicity; europeans; rangahau o te noho-ā-iwi; social conditions; te ao hurihuri; tikanga | indigenous law; tāngata whenua

Chapter Five: Ka Pū Te Ruha, Ka Hao Te Rangatahi: Māori Identities in the Twenty-first Century - Kukutai, Tahu; Webber, Melinda (A land of milk and honey?: making sense of Aotearoa New Zealand, 2017)
"Since colonisation, New Zealand has been mythologised as a 'land of milk and honey' - a promised land of natural abundance and endless opportunity. In the twenty-first century, the country has become literally a land of milk and honey as agricultural exports from such commodities dominate the national economy. But does New Zealand live up to its promise? In this introductory textbook for first year sociology students, some of this country's leading social scientists help us to make sense of contemporary New Zealand. In 21 chapters, the authors examine New Zealand's political identity and constitution; our Māori, Pākehā, Pacific and Asian peoples; problems of class, poverty and inequality; gender and sexualities; and contemporary debates around ageing, incarceration and the environment. The authors find a complex society where thirty years of neoliberal economics and globalising politics have exacerbated inequalities that are differentially experienced by class, ethnicity, gender, sexuality and age. These social divides and problems are at the heart of this text. For sociology students and for a wider audience of New Zealanders, A Land of Milk and Honey? is a lively introduction to where we have come from, where we are now, and where New Zealand society might be headed"--Back cover.
Keywords: census; ethnic identity; identity; social change; social conditions; social life and customs